CIVIL RESPONSIBILITY AND FAKE NEWS - Casé Soares Bezerra, Raissa; Villela Florêncio, Stella (Revista Gênero e Interdisciplinaridade, 2023)
The research aims to analyze civil liability, with a focus related to the dissemination of Fake News, checking the existence, or not, of various damages arising from the conduct of disseminating false news. In this study, we sought to highlight the implications of Fake News, mainly with regard to the theme of freedom of expression, as well as the legality hypotheses, in the Brazilian legal system, culminating in the theme of Civil Liability. The research proposed according to the content analysis technique, states that it is a theoretical research, which will be possible from the content analysis of the doctrine, jurisprudence and relevant legislation. Finally, it remained determined that Fake News is inserted as an element that causes damage, not only moral or material, with the possibility of social damage being visible due to the result of the conduct of disseminating false news in contemporary society.